Design of a concrete mixture with coconut fiber to improve its mechanical properties - Morales Guzmán, Carlos César; Ceballos Vargas, Jesús (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
The present research focuses on the implementation of coconut fibers in concrete mixtures, a material known for its high compressive strength and low tensile strength, which often faces problems such as delayed deformation, drying shrinkage and temperature cracking. By adding coconut fiber, an organic waste material, the aim is to improve the mechanical properties of the concrete. Compressive strength tests were carried out after 28 days on different mixtures. The M-2 mixture, with 0,37% coconut fiber, reached a resistance of 177,387 kg/cm² and a maximum load of 32,625 kg. The M-3 mixture, with 0,55% fiber, presented a resistance of 13,.954 kg/cm² with a load of 24,425 kg. Finally, the M-4 mixture, with 0,74% fiber, achieved a resistance of 158,493 kg/cm² with a load of 29,150 kg. These results suggest that the addition of coconut fiber can improve the strength of concrete, depending on the proportion used.